Feed Composition and Isolate of Histomonas meleagridis Alter Horizontal Transmission of Histomonosis in Turkeys. Proof of Concept - Barros, Thaina L.; Vuong, Christine N.; Latorre, Juan D.; Cuesta, Roberto S.; McGill, Elizabeth; Rochell, Samuel J.; Tellez-Isaias, Guillermo; Hargis, Billy M. (Frontiers in Veterinary Science, 2022)
Outbreaks of histomonosis in turkeys are typically initiated by the ingestion of contaminated embryonated eggs of Heterakis gallinarum, potentially present in earthworms and mechanical vectors. Once an outbreak is started, infected turkeys can transmit the disease by horizontal transmission. Factors influencing horizontal transmission of histomonosis are poorly understood. Replication of horizontal transmission in experimental conditions has not been consistent, presenting an obstacle in searching for alternatives to prevent or treat the disease. Two pilot experiments and three validation experiments were conducted in the present study. In pilot experiment 1, one isolate of Histomonas meleagridis (named Buford) was used. Turkeys were fed a low-nutrient density diet corn-soy based (LOW-CS) and raised in floor pens. In pilot experiment 2, another isolate of H. meleagridis was used (named PHL). Turkeys were fed a low-nutrient density diet with the addition of wheat middlings (LOW-WM) and raised in floor pens. In experiment 3, conducted on floor pens, both isolates and diets were used in different groups. In experiment 4, turkeys were raised on battery cages and only the PHL isolate was used. Both diets (LOW-WM and LOW-CS) were used, in addition to a diet surpassing the nutritional needs of young poults (turkey starter, TS). In experiment 5, conducted in battery cages, only the PHL isolate was used, and the LOW-WM and TS diets were in different groups. The horizontal transmission was achieved only with the PHL isolate from all experiments. The transmission rate varied among experimental diets, with the TS diet having the lowest transmission rate in experiments 4 and 5. Variation was observed between experiments and within experimental groups.